Adsorção do corante verde malaquita utilizando palha de milho modificada por ultrassom - Lima, Diana Ramos (2017)
Colored effluents containing dyes are generated in different industrial sectors, such as textiles, cellulose, paper, leather, paint, among others. The treatment of these effluents is a current environmental problem, since dyes are stable and recalcitrant molecules. In this way, to collaborate in the solution of this problem, the present work aimed the study of Malachite Green (MG )removal from aqueous solutions, by adsorption with raw corn straw (RCS) and ultrasonic modified corn straw (MCS). RCS and MCS were prepared and characterized by XRD, FT-IR, MEV and pHpcz. The adsorption study was performed by equilibrium isotherms, constructed at different temperatures(298 to 328 K), kinetic curves, thermodynamic parameters and application in real effluents composed of dye mixtures and inorganic compounds. The physicochemical interpretations were developed based on the principle of grand canonical ensemble in statistical physics, which considered the following models: multilayer with saturation, double-layer model with two energies and monolayer model with one energy, where thermodynamic functions like configurable entropy (Sa), free adsorption enthalpy (G) and internal energy (Eint) were assessed. The characterization indicated that RCS and MCS presented a favorable structure for malachite green adsorption, as well as that the ultrasonic treatment provided a disorganization of the crystalline regions of the adsorbent, and also, caused the formation of cavities and protuberances. The Elovich model was suitable for adsorption kinetics and the Freundlich model was appropriate to represent equilibrium. The maximum adsorption capacities were 200 mg g-1 for RCS and 210 mg g-1 for MCS, obtained at 328 K. MCS was more effective than RCS to treat real effluents, attaining around 92% of color removal. The double layer model with two energies was the more adequate to represent the adsorption process. The number of MG molecules per site (n) varied from 0.33 to 2.33 and the quantity adsorbed at saturation (Qasat) ranged from 164.15 to 528.19 mg g-1, both of which were increased with temperature. The density of the receptor sites (NM) ranged from 248.71 to 104.88 and decreased with temperature. For RCS and MCS, the first and second energies, ε1 and ε2 increased with temperature, being ε1 greater than ε2. The adsorption energy of MCS (7.77-11.19 kJ mol-1) was higher than the adsorption energy of RCS (6.17-10.88 kJ mol-1). The adsorption process occurred by physisorption and the disorder increased at low equilibrium concentrations but decreased at high concentrations. Free enthalpy and internal energy carefully described the spontaneity of the system studied